PERENCANAAN STRUKTUR GEDUNG ASRAMA MAHASISWA UNIVERSITAS SRIWIJAYA PALEMBANG DENGAN PENAHAN LATERAL DINDING STRUKTURAL - Yudha Putra Ichwandri (Jurnal Teknik Sipil dan Lingkungan, 2014)
The construction in Indonesia has expanded into high-level buildings that require a stable structure, strong enough, capable of serviceability and durability such as those held by the steel structure. However, Indonesia is also a country that has a high intensity earthquake. The earthquake caused storey structure is vulnerable to the occurrence of drift. One method to reduce is by installing of shearwall. Building models are analyzed in terms of 5-shaped building with 5 floors. The measure of building plan is 43,5m x 33m and height is 3,5m. The Function of the building used as dormitory of sriwijaya university. Calculation of structural analysis using SAP 2000 software v.14 in three-dimensional model. The results of this analysis is to know the dimensions, reinforcement plate shear walls and floors. This research produced the conclusion that the the conclusion that in the calculation of the dimensions of the structures obtained dormitory floor slab thickness of 17 cm, and a thickness shear walls and 30 cm. From the result of the calculation have been done, the first until the tenth designs of load combination have their own strength and weakness from several aspect which were being research. Key words : earthquake, dormitory, shearwall,